What Lies Beyond Job Stress and Overload? The Unseen Power of Work-Life Balance in Shaping Job Performance (Case Study of Employee at PT Brantas Abipraya) - UTAMI, VISKHA FUTRY; MAHDY, RAIHAN; HERYADESASTRA, DEDEN; SETIADI, ARIO (Universitas Negeri Semarang, 2025)
The operational effectiveness of state-owned construction enterprises (SOEs) continues to grapple with persistent challenges that may impede achieving projected growth targets for 2025. This research investigates the underexplored mediating effects of employee engagement and job satisfaction in linking work-life balance to job performance, while also analyzing the impact of job stress and work overload on work-life balance—a relationship which previously unexamined in existing literature. Adopting a quantitative-explanatory research design, the study surveyed 266 employees of PT Brantas Abipraya (Persero) using a 4-point Likert scale. Data analysis was conducted through Structural Equation Modeling - Partial Least Squares (SEM-PLS). Key findings reveal that job stress exhibits no statistically significant influence on work-life balance, whereas work overload positively correlates with enhanced work-life balance. Job satisfaction and employee engagement act as partial mediators between work-life balance and job performance, suggesting that these factors amplify—but do not fully account for—the relationship. The partial mediation mechanism underscores a strategic in which organizations must not only prioritize optimizing work-life balance to elevate job performance but also implement targeted strategies to cultivate intrinsic job satisfaction and sustained employee engagement.